The strategy of visual thinking and its applications in teaching arts (photography model): نورا عبد الله علي (Al-Academy, 2019)
The study aims at:1- Identifying the contemporary educational approaches in teaching arts. 2- The effectiveness of using the visual thinking strategy in photography subject for the first year students in the institute of fine arts/Holy city of Kadhimiyah. The study sample is made of (30 ) first year students (in the institute of fine arts/in Holy city of Kadhimiyah) distributed into two groups, an experimental group made of (15) students and a control group having the same number of students in order to conduct the test. The test for the visual thinking strategy in the subject of photography has been designed and the validity and reliability for the research tool have been verified. In order to demonstrate the results of the research, the suitable statistical means have been used. The most important results reached at is that the experimental group which studied according to the visual thinking strategy surpassed the control group which presented a positive indicator for the importance of this strategy